Design and Vibration Isolation Performance of Truss-Type CFRP Raft Frame - Xianglong Wen; Wenhu Li; Yuan Fang; Chunsheng Song; Jinguang Zhang (Shock and Vibration)
Traditional raft frame is single in the form of materials and structures. To give full play to its vibration isolation performance, a truss-type CFRP (carbon fiber-reinforced plastics) raft frame was designed and prepared. Based on the composite material mechanics and damping strain energy model, a method combining the finite element simulation and experiment was used to calculate the damping of the designed CFRP truss structure. The modal harmonic response analysis of CFRP truss structure was carried out by virtue of the ABAQUS finite element software to explore the influence of structure parameters on the vibration transmission characteristics of CFRP truss structure and provide reference for the design of a truss-type CFRP raft frame. The truss-type CFRP floating raft vibration isolation platform was established. Given different excitation sources, the truss-type CFRP raft frame designed in this paper was demonstrated to have good vibration isolation effect in most frequency bands by analyzing the acceleration-vibration level differences.